Internalizing psychopathology and all‐cause mortality: a comparison of transdiagnostic vs. diagnosis‐based risk prediction. Issue 2 (18th May 2021) - Kim, Hyunsik; Turiano, Nicholas A.; Forbes, Miriam K.; Kotov, Roman; Krueger, Robert F.; Eaton, Nicholas R.
Abstract : Previous studies have documented the utility of a transdiagnostic internalizing factor in predicting important future outcomes (e.g., subsequent mental disorder diagnoses). To date, however, no study has investigated whether an internalizing factor predicts mortality risk. Also, while previous studies of mortality risk have emphasized its associations with particular internalizing disorders, no study has assessed how the transdiagnostic internalizing factor vs. disorder‐specific variance differently predict that risk. The primary aims of this study were to explore: a) whether the internalizing factor predicts mortality risk, b) whether particular internalizing psychopathologies uniquely predict mortality risk over and beyond the transdiagnostic internalizing factor, and c) whether there is a significant interaction of internalizing with self‐reported health in the prediction of mortality risk. We utilized a large national sample of American adults from the Midlife in the United States (MIDUS), a longitudinal study that examined midlife development of individuals across multiple waves between 1995 and 2015. Data were analyzed for the 6, 329 participants who completed the phone interview and self‐administered questionnaire in MIDUS 1 (1995‐1996) and were then followed up until October 31, 2015 or until death. To investigate the association between internalizing and mortality risk, we used the semi‐parametric proportional hazards Cox model, where survival time was regressed on a latent internalizing factor. Overall findings indicate that a transdiagnostic internalizing factor significantly predicts mortality risk over a 20‐year period (hazard ratio, HR=1.12, 95% CI: 1.05‐1.16, p<0.01) and that internalizing outperforms disorder‐specific variance (e.g., depression‐specific variance) in the prediction of that risk. Further, there was a significant interaction between transdiagnostic internalizing and self‐reported health, whereby internalizing psychopathology had a specific association with early death for individuals with excellent self‐reported health condition (HR=1.50, 95% CI: 1.17‐1.84, p<0.05). This highlights the clinical utility of using the transdiagnostic internalizing factor for prediction of an important future outcome, and supports the argument that internalizing psychopathology can be a meaningful liability to explore in public health practice.